An Investigation of Fiat Characterization and Evolutionary Dynamics of the Cryptocurrency Market - DÖNMEZ, CEM ÇAĞRI (SAGE PUBLICATIONS INC, 2021)
Recent developments in global financial markets revealed that cryptocurrencies experienced rapid growth due to the popularity of blockchain technology and its evolving position in the digital finance industry. The rise of cryptocurrencies led economists to question generally accepted financial practices. Particularly the interaction between two different types of financial markets arose as a hot research topic to discover specific relationships and differences between major cryptocurrencies and fiat currencies. Therefore, this article aims to examine analyze by attaching importance to the Bitcoin to investigate significant linkages and analyze critical direct and indirect connections. In this research, Bitcoin-which is known as the most prominent cryptocurrency on the market-and 50 different conventional currencies are taken into consideration by applying cross-correlation, HT (hierarchical tree), and MST (minimum spanning tree) methods. The results of this work can be utilized by academicians and economists for further research related to the subject.
Keywords: blockchain; cryptocurrencies; Bitcoin; fiat currencies; cross-correlation; minimum spanning tree; hierarchical tree